1985
DOI: 10.1126/science.3892686
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic-Aromatic Interaction: A Mechanism of Protein Structure Stabilization

Abstract: Analysis of neighboring aromatic groups in four biphenyl peptides or peptide analogs and 34 proteins reveals a specific aromatic-aromatic interaction. Aromatic pairs (less than 7 A between phenyl ring centroids) were analyzed for the frequency of pair type, their interaction geometry (separation and dihedral angle), their nonbonded interaction energy, the secondary structural locations of interacting residues, their environment, and their conservation in related molecules. The results indicate that on average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

77
1,649
1
12

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,439 publications
(1,739 citation statements)
references
References 25 publications
77
1,649
1
12
Order By: Relevance
“…We found that the main reason for this behavior was the carbon-carbon function u ab (r ab ) of eqn (3). Therefore, for r ab r r max , where r max is the point where u CC reaches its maximum, this function was set to a constant value, equal to its value at r max E 2.5 Å .…”
Section: A Analytic Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the main reason for this behavior was the carbon-carbon function u ab (r ab ) of eqn (3). Therefore, for r ab r r max , where r max is the point where u CC reaches its maximum, this function was set to a constant value, equal to its value at r max E 2.5 Å .…”
Section: A Analytic Fitmentioning
confidence: 99%
“…The interactions between aromatic systems are of special interest, since they can play an important role in determining protein and DNA stability [1][2][3][4] and DNA-protein interaction. 5,6 The benzene dimer has received much attention both from experimentalists [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] and theorists.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, peptides that contain Asx turns require Pro to further support the unique turn conformation. The surprising stability of F4-Asn suggests other stabilizing factors such as Tyr aromaticaromatic interactions (Burley & Petsko, 1985) or Tyr phenolic hydrogen bonding to a charged side chain may be involved in stabilizing this peptide as suggested for F4-6.…”
Section: Discussionmentioning
confidence: 91%
“…Because precedent shows that a Tyr interaction is possible with Glu in a helix (Ramachandran et al, 1971), Asp may impose the same restrictions here as it does when hydrogen bonding with Lys, i.e., interacting more favorably in an aL-helical conformation. Lastly, the high content of Tyr residues may further enhance the stability of the lefthanded helix by aromatic-aromatic interactions (Burley & Petsko, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing body of evidence indicates that the ability of aromatic rings to serve as hydrogen-bond acceptors is real and significant to the structure and function of proteins (Burley & Petsko, 1985;Levitt & Perutz, 1988). Our work suggests that highly inaccurate simulations may result if the capacity to form such bonds is not incorporated into aromatic models.…”
Section: (Ps)mentioning
confidence: 90%